Market access and value chain analysis of dairy industry in Ethiopia: The case of Wolaita Zone - Kuma, B. (Haramaya University, 2012)
Market access and value chain of dairy products in Wolaita zone was analyzed to identify and prioritize constraints and come up with strategic interventions, to identify determinants of participation decision and level of participation in-farm level milk value addition, to assess factors affecting milk sales decision and access to alternative milk market outlet choices, to identify determinants of fluid milk purchasing sources and to identify factors affecting unpacked and packed fluid milk consumption. Secondary data sources used include journal articles, books, CSA, internet, national policies, zonal and wereda reports. Primary data were collected using participatory, rapid market appraisal and survey from random samples of 398 farmers, 198 consumers, 79 traders and 53 hotels/restaurants. The results show that farmers produced mean milk yield of 8 liters per day, out of which 27.8% was used for home consumption, 58.2% was sold to market outlets and 26.6% was used for value addition. About 27.9%, 22.1%, and 9.4% of the milk produced per day was sold to consumers, hotels/restaurants and cooperatives, respectively. The first-stage probit model results indicate that milk yield in liter per day, distance from urban centers, age, child, poor access to livestock extension services, shelf life, social factors (holidays and fasting), and labor availability determined household‟s decision to add values to milk. Heckman second stage results show that most of the factors determining decision of participation in milk value addition also determined the level of participation. The probit model results indicate that household size, presence of a child, landholding size, distance from urban center and milk yield per day played a significant role in the probability of milk sales decision. Conditional (fixed-effect) logistic model results indicate that compared to accessing individual consumer market outlet, the probability of accessing cooperative market outlet was higher for households who had better access to livestock extension services, many years of farming experiences, large landholding size and members to cooperative. Compared to accessing individual consumer market outlet, the probability of accessing hotels/restaurants market outlet was higher for households who had better access to livestock extension services and who owned large number of cows. Multinomial logit model results indicate that age of household head, household income, presence of a child, households who disagree with the statement „packed fluid milk is fattening‟, households who disagree with the statement „advertisement influences people so they buy fluid milk‟, who agree with the statement „price of packed fluid milk is expensive compared with unpacked fluid milk‟ and who own cows impacted consumption of unpacked fluid milk. Education level of household head, young aged household heads, households with at least a member who has medical prescription, households who accept the statement „sterilized milk contains preservatives‟ consumed packed fluid milk. Shortage of feed, low cattle productivity and genetics, inadequate extension services, inadequate institutional support and veterinary services were major constraints. Fodder trees and mixed tree legume protein banks, efficient breeds selection that adapt to the environment, appropriate technical and institutional support and capacity improvement are steps to improve dairy value chain.